Decompositions of complete 3-uniform hypergraphs into small 3-uniform hypergraphs - Bryant,D.E. (University of Queensland Press, 2015)
© 2014, University of Queensland. All Rights Reserved. In this paper we consider the problem of determining all values of v for which there exists a decomposition of the complete 3-uniform hypergraph on v vertices into edge-disjoint copies of a given 3-uniform hypergraph. We solve the problem for each 3-uniform hypergraph having at most three edges and at most six vertices, and for the 3-uniform hypergraph of order 6 whose edges form the lines of the Pasch configuration.